The agenda premises of the judicialization of politics: policy attention in Israel’s high court of justice - Maoz Rosenthal; Assaf Meydani (Frontiers in Political Science)
This study examines the supposed “activism” of Israel’s High Court of Justice amid recent political crises and legislative efforts to curb its powers. While judicial behavior often balances political activism and constitutional problem-solving, this paper analyzes the Court’s agenda structure to assess its approach. The research hypothesizes that an activist court would maintain an agenda focused on a few core topics over time. In contrast, a court that takes a legal, constitutional approach would have an agenda with a broad array of topics and policy punctuations. Analyzing the Court’s rulings from 1995 to 2018, this study reveals an agenda structure mostly aligning with the latter expectation. By examining the dynamics of policy attention, this paper contributes to our understanding of judicial review strategies beyond traditional preference and incentive-based models. The findings suggest that Israel’s High Court of Justice usually operates more as a legal problem solver than an activist institution, offering new insights into its role in Israeli politics and policymaking.